Exploring The Speaking Anxiety Among English Language Education Undergraduate Students at Universitas Negeri Malang - Nur Giana Febrianti; Nurenzia Yannuar; Yusnita Febrianti (Didaktika: Jurnal Kependidikan, 2025)
Speaking anxiety is a prevalent challenge in foreign language learning that can hinder students’ ability to communicate effectively. This study investigates the causes of speaking anxiety among undergraduate students in the English Language Education program at Universitas Negeri Malang. Employing a qualitative descriptive design, data were collected from 11 participants through the Foreign Language Classroom Anxiety Scale (FLCAS) questionnaire and semi-structured interviews. The data were analyzed using thematic analysis to identify recurring patterns and factors contributing to students’ anxiety. The findings reveal three primary sources of speaking anxiety: communication apprehension, test anxiety, and fear of negative evaluation. Students reported experiencing physiological symptoms such as a rapid heartbeat, nervousness, and fear of being mocked, which significantly influenced their classroom participation and speaking performance. These results highlight the urgent need for supportive pedagogical strategies that not only enhance students’ linguistic competence but also address their psychological and emotional well-being. The study contributes to a deeper understanding of the multidimensional nature of speaking anxiety and provides insights for educators in developing effective interventions to foster more confident English communication among students.